Optimization of Stir Casting of Aluminum Matrix Composites (AMCs) with Filler of Recycled Glass Powder (RGP) for The Mechanical Properties - Hendronursito, Yusup; Rajagukguk, Tumpal Ojahan; Anshori, Anang; Yunanto, Asep (Universitas Negeri Malang, 2020)
A study of making Aluminum Matrix Composites (AMCs) uses recycled glass powder (RGP) as a filler has been carried out through the stir casting process. The experimental design uses the Taguchi method of 3^3 orthogonal array L9 with the parameters of powder size (20>x> 80, 80>y> 200, 200>z> 325), percentage of filler vs matrix (2%, 7%, 12%), and stirring time (30 Seconds, 3 Minutes, 12 Minutes). The optimum conditions for the hardness of Al-GRp composites were obtained from specimens with Mesh powder size parameters 200> z> 325, the percentage of glass vs aluminum powder was 12% wt, stirring time was 12 minutes. The experimental factor that has the greatest contribution to the hardness value of Al-GRP composites is the size of glass powder of 73.77%, followed by the percentage of glass powder to aluminum by 19.98%, and the stirring time of 1.21%. The optimum experimental parameters for tensile strength can be obtained from specimens with particle size parameters of 20> x> 80, the percentage of glass powder to the weight of aluminum 12%, and the stirring time of 30 seconds. The biggest contribution to the tensile strength value of the Al-GRP composite was the stirring time of 72.71%, followed by the percentage of glass powder to aluminum by 13.67%, and the size of the powder was 9.97%.